The Impact of Investment Policy in a Changing Global Economy : A Review of the Literature - Echandi, Roberto; Krajcovicova, Jana; Qiang, Christine Zhenwei (World Bank, Washington, DC, 2015)
Evidence shows that foreign direct investment can provide many benefits to host countries, including productivity improvements, better jobs, and knowledge transfer. Further, it can serve as a vehicle for transformation of domestic production and better integration with global value chains. Nonetheless, these benefits are not automatic. Investment policies are required to maximize the potential gains of foreign direct investment. One challenge is that there are different kinds of foreign direct investment, and each may have different economic, social, and environmental impacts. However, the literature analyzing foreign direct investment often tends to swing from an extremely case-specific focus — analyzing experiences in one particular country in a single sector during a given period — to lumping together the analysis as if it was a homogenous phenomenon. Investment policy formulation requires a framework sophisticated enough to differentiate between the various kinds of foreign direct investment, as well as potential challenges and benefits for development. It must also be simple enough to enable governments to organize and prioritize the multiple and complex variables affecting the maximization of investment benefits. This paper presents an overview of the literature on the impact of foreign direct investment. The paper argues that a logical framework is needed to organize existing evidence from research to fill gaps in the literature and make existing evidence more useful in targeting policy making.